Analyzing Gender Differences in Consumer Perception and Preferences for African Prints in Southwest Nigeria - Adebayo Abiodun Adeloye, (Interdisciplinary Journal of Management and Social Sciences, 2024)
This research investigated consumer behaviour towards African Print fabrics in Southwest Nigeria. With an emphasis on gender differences, the study examined the factors responsible for consumer perception and preferences. African print is deeply rooted in Nigeria's rich cultural heritage and serve as a lens through which to explore the consumer choices. Survey research design was adopted for the study using questionnaire as the data gathering tool. Samples were selected across the six states in Southwest Nigeria. A total of three hundred and eighty-four (384) African print consumers were sampled using random sampling technique. The data was subjected descriptive analysis, using frequency distribution, percentage, and mean score. The study revealed that both male and female users of African print fabrics have similar African print preferences with slight differences such as brands and colour choices. It was therefore recommended that African print designers should focus on consumer preferences during the design process of African print fabrics.